Importancia pronóstica de las mutaciones del gen promotor de la transcriptasa inversa de la telomerasa en los meningiomas de alto grado. - Cañas, Alejandro; Jiménez, Enrique; Hakim, Fernando; Armando Mejía, Juan; Fernando Ramón, Juan; Gómez, Diego; Jaramillo-Velásquez, Daniel; Bermúdez, Sonia; Useche, Nicolás; Pineda, Diego; Cifuentes, Hernando; Becerra, Antonio; et al. (Biomédica: Revista del Instituto Nacional de Salud, 2022)
Introduction: Mutations in the promoter region of telomerase reverse transcriptase occur frequently in meningiomas. Objective: To estimate the prognostic importance of telomerase reverse transcriptase mutations in Colombian patients with grades II and III meningioma. Materials and methods: This was a multicenter retrospective cohort study of patients diagnosed with refractory or recurrent WHO grades II and III meningiomas, recruited between 2011 and 2018, and treated with systemic therapy (sunitinib, everolimus ± octreotide, and bevacizumab). Mutation status of the telomerase reverse transcriptase promoter was established by PCR. Results: Forty patients were included, of which telomerase reverse transcriptase mutations were found in 21 (52.5%), being C228T and C250T the most frequent variants with 87.5 % and 14.3 %, respectively. These were more frequent among patients with anaplastic meningiomas (p=0.18), with more than 2 recurrences (p=0.04); and in patients with parasagittal region and anterior fossa lesions (p=0.05). Subjects characterized as having punctual mutations were more frequently administered with everolimus, sunitinib and bevacizumab drug series (p=0.06). Overall survival was 23.7 months (CI 13.1-34.2) and 43.4 months (CI 37.5-49.3; p=0.0001) between subjects with and without mutations, respectively. Multivariate analysis showed that the number of recurrences and the presence of telomerase reverse transcriptase mutations were tthe only variables that negatively affected overall survival. Conclusions: Mutations in telomerase reverse transcriptase allows the identification of high-risk patients and could be useful in the selection of the best medical treatment.